Cultural Dissonance: Surfers' Environmental Attitudes and Actions - Langseth, Tommy; Vyff, Adam (Frontiers in Sports and Active Living, 2021)
Surfers often see themselves as “green”. In this study we examine Norwegian surfers' attitudes and actions towards the environment. The article is based on a questionnaire (n = 251) and six qualitative interviews. The results show that most surfers see themselves as environmentally conscious. Oppositely, the data also show that they also buy a lot of surf-related apparel and equipment and travel a lot, and thereby contribute with a lot of CO2-emissions. In the article we investigate the apparent attitude-action gap amongst surfers. Does the gap give rise to emotional conflicts? And, if so, to what degree and how do they cope with it. In the article we start out by analysing such potential conflicts by using the concept cognitive dissonance. Further, we analyse the phenomena from a cultural, Bourdieusian perspective where values within the surf-field is highlighted. On the one hand, surf culture highly values connexion to nature and “green” thinking, on the other hand it also values and gives recognition to surfers that travels to and explore exotic destinations. Hence, values within surf culture leads surfers to conflicting actions. We end the article by discussing if these conflicts could be framed as cultural dissonance.